The Influence of Market Segmentation and Targeting on Purchase Decisions of Youth Angkringan Businesses in Wonodadi District, Blitar - Sulchan, Moch; Rahmawati, Anis (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This study aims to determine the impact of market segmentation and targeting strategies on the purchasing decisions of Youth Angkringan enterprises in Wonodadi District, Blitar. The study investigates how these factors influence purchase decisions using a quantitative, associative research approach. The sample comprises 100 respondents, selected through a saturated sampling technique from the entire population. Primary data was collected via questionnaires distributed to Youth Angkringan businesses in the district. SPSS 23 was used to perform path analysis, with a significance level set at 0.05. The findings reveal that market segmentation has a significant and positive effect on the purchasing decisions of Youth Angkringan enterprises in Wonodadi District. Additionally, the target audience also plays a crucial and beneficial role in shaping purchasing decisions for these businesses